Intestinal Fatty Acid Binding Protein Levels in Pediatric Celiac Patients in Transition From Active Disease to Clinical and Serological Remission. Issue 2 (30th May 2021) - Hoofien, Assaf; Guz-Mark, Anat; Zevit, Noam; Tsadok Perets, Tsachi; Assa, Amit; Layfer, Olga; Matar, Manar; Nachmias-Friedler, Vered; Silbermintz, Ari; Shamir, Raanan
Abstract : Objectives: Celiac disease (CD) is increasingly diagnosed without endoscopy. As such, the need for accurate serological markers to aid in the diagnosis and follow-up of CD has increased. Intestinal fatty acid binding protein (I-FABP) is a cytosolic protein present in enterocytes, whose blood levels reflect mucosal damage in a reliable and quantifiable way. The aim of this study was to compare I-FABP levels in newly diagnosed patients with CD and to examine changes in levels following 6 months of gluten-free diet (GFD). Methods: A prospective observational case control study of pediatric patients diagnosed with CD, with measurements of tissue transglutaminase IgA (TTG-IgA) and I-FABP levels at diagnosis and after 6 months of gluten free diet were compared to a control group of nonceliac patients. Results: This study included 35 patients and 32 controls. The CD group had higher I-FABP levels at diagnosis compared with the control group (median 641.7 pg/mL versus 334 pg/mL; P  < 0.05). I-FABP levels significantly differed between patients presenting with TTG-IgA level 3–10 times the upper limit of normal (ULN) compared with those presenting with values >10 times ULN (median 432.2 pg/mL versus 796.2 pg/mL; P  < 0.05). Patients with CD had a significant decrease in median I-FABP levels after 6 months of GFD (median 268.2 pg/mL), paralleling a decrease in TTG-IgA and GFD adherence. Conclusions: I-FABP levels are increased in patients with CD at diagnosis compared with controls and decrease significantly while patients adhere to GFD.